Pornography and Speech Act Theory – An In-Depth Survey - Áron Dombrovszki (Elpis)
Considering the short history of the feminist philosophy of language, Rae Langton’s article “Speech Acts and Unspeakable Acts” was highly influential as one of the first positive research programs in the movement. In her paper, Langton – using John L. Austin’s speech act theory – interprets Catharine MacKinnon’s thesis: pornography is a speech that subordinates and silences women. Despite the importance of the subject, those unfamiliar with certain historical and contextual features of the topic would hardly understand it.